New Zealand Crown Company boards: director perceptions of selection processes, board composition, director attributes and diversity : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Business and Administration in Corporate Governance at Massey University, Manawatu Campus, New Zealand - Quince, Julia Georgina (Massey University, 2010)
This research focuses on the governance of New Zealand Crown Company Boards. In-depth interviews were carried out with 23 Crown directors and 20 specialist commentators to ascertain their perceptions of board selection processes, board composition and director attributes required for the governance role, with particular consideration given to diversity. Content analysis of transcribed interview data allowed for a qualitative exploration of insights as well as some calculations to augment and quantify the weighting of opinion. The research found, in the views of directors and specialist commentators, boards should be comprised of directors who already possess a range of financial and other ‘hard’ business skills. Comments on the need for business skills heavily out-weighed discussion of soft skills and ethics. Respondents believed directors should be appointed on merit, based on their record in business and related fields, rather than on a broader set of criteria that might encourage greater consideration of board diversity. The study found directors also perceive governance training should be undertaken to ensure skills remain current. It was noted that there is an inevitable political overlay within the New Zealand Crown Company structure, which limits transparency. The study concluded that the current approach to appointments is likely to result in a restricted pool of directors, which in turn limits diversity and with it the potential of achieving an optimal mix of relevant knowledge and skills. Further, current training mechanisms do not support the opportunities for new directors to embark on directorships. The research recommends that the Crown Ownership Monitoring Unit expand the current emphasis on recruiting for commercial and business expertise to include targeted recruitment of candidates from non-traditional sources/communities, thus genuinely enhancing diversity and building board capability. The research also recommends that this initiative be supported by a Director Internship scheme whereby unproven or inexperienced candidates from non-traditional career and cultural backgrounds, are encouraged to apply for positions on Crown Company boards and that COMU works with governance training organisations to provide targeted training and ongoing mentoring support throughout the internship.
Keywords: New Zealand Crown Company boards; Boards of directors; Corporate governance; New Zealand; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management